Islamic psychology human behaviour and experience from an Islamic perspective - Rassool, G. Hussein (Abingdon, Oxon New York, NY Routledge, 2021)
Islamic Psychology or ilm an-nafs (Science of the Soul) is an important introductory textbook drawing on the latest evidence in the sub-disciplines of psychology to provide a balanced and comprehensive view of human nature, behaviour and experience. Its foundation to develop theories about human nature is based upon the writings of Muslim scholars and contemporary research findings. Synthesising contemporary empirical psychology and Islamic Psychology, this book is holistic in both nature and process and includes the physical, psychological, social and spiritual dimensions. Through a broad and comprehensive scope, the book addresses three main areas: context, perspectives and the clinical applications of applied psychology from an Islamic approach. This book is a core text on Islamic psychology for undergraduate and post-graduate students and those undertaking continuing professional development in Islamic psychology, psychotherapy and counselling. Beyond this, it is also a good supporting resource for teachers and lecturers in this field"--
Includes bibliographical references and index.
Keywords: Islam -- Psychology; Psychology -- Methodology